Transcript of Interview Chair of COE - Turkana South, Lokichar - Kinyera, Paddy Banya (Oil Movements: the Production and Government of Petro-(im)mobilities in East Africa, 2020)
Translated transcription
Keywords: Mega Infrastructure; Lamu Port and Lamu-Southern Sudan-Ethiopia Transport Corridor; Kenya